Pengaruh Current Ratio, Debt To Total Asset Ratio, dan Net Profit Margin Terhadap Financial Distress pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2011-2014 - Marita Indah Sari Pratama; Myrna Sofia (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2018)
The purpose of this study is to determine the effect of Current Ratio, Debt to Total Asset Ratio, and Net Profit Margin to Financial Distress in manufacturing companies listed on the Indonesia Stock Exchange for the period 2011-2014. The results of this study indicate that the Persial Current Ratio has a significant effect on Financial Distress. While the Debt to Total Asset Ratio does not significantly influence the Financial Distress. While the Net Profit Margin has a significant effect on Financial Distress. Simultaneously Current Ratio, Debt to Total Asset Ratio and Net Profit Margin have a significant effect on Financial Distress. This is evidenced by the determinant coefficient of loading with the adjusted R2 value of 0.196. This shows that 19.6% of the Financial Distress is influenced by Current Ratio, Debt to Total Asset Ratio and Net Profit Margin and the remaining 80.4% is influenced by other variables not reviewed in this study